Epidemiology of Substance Use among Forced Migrants: A Global Systematic Review. - Danielle Horyniak; Jason S Melo; Risa M Farrell; Victoria D Ojeda; Steffanie A Strathdee (PLoS ONE, 2016)
Introduction Forced migration is occurring at unprecedented levels. Forced migrants may be at risk for substance use for reasons including coping with traumatic experiences, co-morbid mental health disorders, acculturation challenges and social and economic inequality. This paper aimed to systematically review the literature examining substance use among forced migrants, and identify priority areas for intervention and future research. Methods Seven medical, allied health and social science databases were searched from inception to September 2015 in accordance with PRISMA guidelines to identify original peer-reviewed articles describing any findings relating to alcohol and/or illicit drug use among refugees, internally displaced people (IDPs), asylum seekers, people displaced by disasters and deportees. A descriptive synthesis of evidence from quantitative studies was conducted, focusing primarily on studies which used validated measures of substance use. Synthesis of evidence from qualitative studies focused on identifying prominent themes relating to the contexts and consequences of substance use. Critical Appraisal Skills Programme (CASP) checklists were used to assess methodological quality of included studies. Results Forty-four quantitative (82% cross-sectional), 16 qualitative and three mixed-methods studies were included. Ten studies were rated as high methodological quality (16%), 39 as moderate quality (62%) and 14 as low quality (22%). The majority of research was conducted among refugees, IDPs and asylum seekers (n = 55, 87%), predominantly in high-income settings. The highest-quality prevalence estimates of hazardous/harmful alcohol use ranged from 17%-36% in camp settings and 4%-7% in community settings. Few studies collected validated measures of illicit drug use. Seven studies compared substance use among forced migrants to other migrant or native-born samples. Among eight studies which conducted multivariable analysis, male sex, trauma exposure and symptoms of mental illness were commonly identified correlates of substance use. Conclusion Our understanding of substance use among forced migrants remains limited, particularly regarding persons displaced due to disasters, development and deportation. Despite a growing body of work among refugee-background populations, few studies include refugees in low and middle-income countries, where over 80% of the global refugee population resides. Findings suggest a need to integrate substance use prevention and treatment into services offered to forced migrants, particularly in camp settings. Efforts to develop and evaluate interventions to reduce substance use and related harms are needed.